CLIMATE CHANGE IMPACTS ON AGRICULTURAL WATER MANAGEMENT: CHALLENGE FOR INCREASING CROP PRODUCTIVITY IN SERBIA - Đuričin, Sonja; Savić, Slađana; Bodroža, Duško; Cvijanović, Gorica; Đorđević, Slaviša (Economics of Agriculture, 2016)
Years which are encompassed by the research, according to the mean daily air temperatures and precipitation, were characterized by the frequent occurrence of extremely warm and dry vegetation periods. The aim of the research is to estimate the economic viability of the production of maize, potatoes and tomatoes in terms of FI (full irrigation). The assessment of the economic viability of the application of the irrigation system when it comes to maize and potato production is done on the basis of a comparative analysis of the realized proft in the natural water regime and FI, whereas in the case of greenhouse tomato production it is done on the basis of comparative analysis of proft achieved in terms of RDI (regulated defcit irrigation) and FI. The research results indicate a positive economic effect of the irrigation system implementation because in our climate the water needs of a culture cannot be satisfed solely by precipitation, and thus water defcit occurs. This lack of rainfall causes yield reduction because it is the main parameter which increases the production proftability. Therefore, increasing the area under irrigation is very important.